BEHAVIOURAL RISK FACTORS AND HEALTHY LIFE EXPECTANCY AT OLDER AGES: EVIDENCE FROM ELSA AND HRS. (11th November 2018) - Zaninotto, P; Head, J; Steptoe, A
Abstract: The aim of this study was to examine the extent to which the co-occurrence of smoking, physical inactivity, alcohol consumption and obesity predict healthy life expectancy and whether these factors show different associations with healthy life expectancy in 10, 388 individuals from ELSA and 17, 351 from HRS, using harmonized datasets from 2002–2013. Multistate life table models were used to estimate sex-specific disability-free and chronic disease-free life expectancy, adjusted for wealth. Individual and co-occurring behavior-related risk factors are strongly associated with shorter healthy life expectancy in both countries. Those with no behavior-related risk factors could expect to live on average up to 10 years longer without disability. Patterns are similar in England and in the US; however, people in the US have considerably shorter chronic disease-free life expectancy than English people. Obesity and physical inactivity contributed to the greatest reduction in chronic-disease free life expectancy and smoking in disability-free life expectancy.